Developing energy production from Eucalyptus urophylla plantation in dryland ecosystem at East Nusa Tenggara, Indonesia - Ronggo Sadono; Wahyu Wardana; Fahmi Idris; Pandu Yudha Adi Putra Wirabuana (Journal of Degraded and Mining Lands Management, 2023)
Forest rehabilitation of Timor Island's dryland ecosystems using eucalyptus plants plays an important role in improving land cover but also in mitigating climate change and providing an alternative renewable energy source. The aim of this study is to explore the enormous energy storage potential of eucalyptus plants for commercial purposes using a high spatial resolution remote sensing approach. The Pléiades satellite imagery acquired on 10/09/2021 covering ca. 27 ha study area managed by Timor Tengah Selatan Forest Management Unit was used to identify the density of eucalyptus plants using Normalized Difference Vegetation Index (NDVI) values greater than 0.699. The density of eucalyptus plants is classified into low, moderate, and high tree density with NDVI values greater than 0.699 to 0.765, greater than 0.765 to 0.833, and greater than 0.833 to 0.901, respectively. The total potential energy production of the study area was estimated using a combination of assumed eucalyptus tree density, the calculated area of each density, and the average energy storage of individual trees. The results showed that the density of eucalyptus trees was classified as low, moderate, and high, with coverage areas of 6.8 ha, 12.9 ha, and 3.0 ha, respectively. The potential energy production of low, moderate, and high density approaches 1,103,432.33 MJ; 5,522,999.19 MJ; and 2,120,715.04 MJ, respectively, with a total estimated energy storage of 8,747,146.57 MJ. This obtained number of potential energy estimations indicates that forest rehabilitation of dryland ecosystems through eucalyptus plantations has a promising future as an alternative renewable energy source.